Pregnancy outcomes in women with primary ovarian insufficiency in assisted reproductive technology therapy: a retrospective study - Sun, Bo; Li, Lu; Zhang, Yile; Wang, Fang; Sun, Yingpu (Frontiers in Endocrinology, 2024)
To retrospectively estimate cumulative reproductive outcomes in women with primary ovarian insufficiency (POI) in Assisted reproductive technology(ART)therapy.A total of 139 patients diagnosed with POI were reviewed in this study. Firstly, they were divided into 2 groups according to oocyte origin: using their own oocytes (OG group) or accepting oocytes donation (OD I group). Secondly, the patients were split depending on pregnancy outcome. In the OG group, 9 patients decided to use others' oocytes after a failure of attempting to use their own, and this population was the oocytes donation II group (OD II group).There were 88 patients who used their own oocytes, while 51 patients accepted oocytes donation.In OG group, there are only 10 (7.2%) patients got pregnant, and patients in OD group had worse hormone levels (FSH 71.37±4.18 vs 43.98±2.53, AMH 0.06±0.04 vs 1.15±0.15, and AFC 0.10±0.06 vs 1.15±0.15) and more years of infertility (5.04±0.48 vs 3.82±0.30), which explained why they choose oocyte donation. In all the three groups, baseline characteristics were comparable between pregnant women and non-pregnant women. Of the ten pregnant patients in OG group, four of them used luteal phase short-acting long protocol and had pregnancies successfully in their first cycles.Ovarian stimulation in POI women require more cost and time. For those with stronger desire to have genetic offspring, luteal phase short-acting long protocol may help them obtain pregnancy rapidly.